(untitled) (Journal of Pharmaceutical Negative Results, 2022)
AIM: The aim of this study, was to check the effect of variation in media incubation time on progressive motility of spermatozoa of men attending Acharya Vinoba Bhave Rural Hospital, Wardha Testube Baby Center. METHOD: A total 55 semen samples of patients were used in this study. Semen Analysis was performed according to WHO guidelines 2010 and observations for Sperm Count and motility was recorded as Pre-wash data. Sperm Processing was performed using density gradient method in which samples randomly divided into 3 group with media of variant incubation time at 37oC-36oC (i.e. 18 samples in ±15 min; 19 samples in ±30 min; 18 samples in ±60 min), and observations for Sperm Count and motility was recorded as Post-wash data. Retrieval rate of progressive motility of sperm in all 3 groups were evaluated and compared via Pre and Post wash data. RESULT: A timeline of individual sample in all three groups was recorded to trace the lower limit, upper limit and average retrieval rate of the group. For group with media incubation time ±15Min, upper limit value was 24%; lower limit value was 0.56% and average of progressively motile sperm retrieval rate was 8.26%. For group with media incubation time ±30Min, upper limit value was 23.3%; lower limit value was 2.0% and average of progressively motile sperm retrieval rate was 8.22%. For group with media incubation time ±60Min, upper limit value was 17.6%; lower limit value was 2.1% and average of progressively motile sperm retrieval rate was 8.14%. Variation in incubation time of sperm preparation media affects the retrieval rate of progressive motility sperms from the native semen sample which subsequently may influence the assisted reproductive technology (ART) outcomes. Sperm Processing media should be incubated at 37oC-36oC for ±15min for better retrieval outcome.